Anaesthetic Considerations in Managing Renal cell Carcinoma in a Resource-Poor Setting - Fiekabo, Hart; Victor, Abhulimen (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Renal Cell Carcinoma (RCC) accounts for 2% of global cancer diagnoses and deaths, its incidence is increasing globally. In Africa, the incidence of RCC is relatively low but many patients present late with advanced-stage disease and consequently, poorer prognosis. Anaesthetic care of these patients is important. Materials and Methods: This is a ten-year retrospective study conducted at the University of Port Harcourt Teaching Hospital. Ethical approval for the study was sought and gotten from the hospital’s ethical committee. The information gotten includes the type of anaesthesia and method of postoperative pain management. The data collected was analyzed and presented in a table. Results: 84% had general anaesthesia while 16% had regional anaesthesia, all the patients had multimodal method of pain management. Conclusion: Perioperative management for renal surgery varies significantly depending on the disease and patient groups, the anaesthetic must take into consideration the various surgical approaches and be prepared to assist the surgeon.